Spousal intimacy, type of antiretroviral drug and antiretroviral therapy adherence among HIV patients in Bandung, Indonesia - Safitri Fadilla Wardhani; Sri Yona (SAGE Publishing, 2021)
Background: Antiretroviral therapy (ART) has been proven effective in reducing the mortality rates among people living with HIV/AIDS (PLWH). However, poor adherence to ART may result in treatment failure. Few studies examine the relationship between spousal intimacy, type of ART and ART adherence. This study aimed to investigate the association between spousal intimacy, type of antiretroviral therapy (ART) and antiretroviral therapy adherence among PLWH in Bandung, Indonesia. Design and Methods: A cross-sectional study was conducted involving 115 adult PLWH who were receiving ART at least for 6 months in RSUD Kota Bandung, they were selected with consecutive sampling.  The data were analyzed using chi-square test. Results: The majority of PLWH (61.74%) reported had high level of spousal intimacy, about 93.91% PLWH used first line of ART, and 88.69% had high adherence in consuming ART. Spousal intimacy had a significant relationship to antiretroviral adherence (p<0.001) and type of ART (p=0.031, OR: 7.35) significantly associated with antiretroviral adherence. Conclusions: PLWH who have high levels of spousal intimacy also have high levels of antiretroviral adherence. PLWH on first-line ART were 7.3 times more adherent on ART.